Wavelength switchable and stable single-longitudinal-mode erbium-doped fiber laser based on Mach–Zehnder interferometer and tunable filter. Issue 1 (2nd January 2018) - He, Wei; Zhu, Lianqing; Dong, Mingli; Luo, Fei
Abstract: An erbium-doped fiber laser with all-fiber Mach–Zehnder interferometer (MZI) and tunable filter was proposed and experimentally demonstrated. In the designed fiber laser, 6 m C-band erbium-doped fiber was selected as a gain medium; the MZI comprised two waist-enlarged fiber bitapers. In the experiment, the laser threshold was 93 mW, whereas a switchable single-longitudinal-mode laser was realized within 1519.7–1564.6 nm by adjusting the tunable filter and the line interval was less than 2.5 nm; for single-wavelength laser, the peak power difference of each line was less than 4 dB, and the power fluctuation was less than 0.77 dB within 10-min scan time. A stable and switchable dual-wavelength laser was realized, the wavelength spacing of each dual-wavelength laser was less than 0.7 nm, the side-mode suppression ratio was more than 30.2 dB, and the power shift was less than 0.39 dB. The laser's 3-dB linewidth was less than 0.1 nm.